Absorbable Metals for Biomedical Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Absorbable metals have shown significant clinical potential for temporary implant applications, where the material is eventually replaced by healthy, functioning tissue. However, several challenges remain before these metals can be used in humans. Innovations and further improvements are required. This book collects scientific contributions dealing with the development of absorbable metals with improved and unique corrosion and mechanical properties for applications in highly loaded implants or cardiovascular and urethral stents.